1997
DOI: 10.1007/bf02490517
|View full text |Cite
|
Sign up to set email alerts
|

Separation of polar compounds by solvating gas chromatography with carbon dioxide mobile phase

Abstract: SummaryIn this study, the separation of polar compounds in solvating gas chromatography (SGC) was investigated. Capillary columns (250 gm i.d.) packed with deactivated siliceous particles, including SE-54 encapsulated silica particles, diol-bonded silica particles, and polyethylenimine (PEI) coated particles, and nonsiliceous particles of styrene-divinylbenzene were used. Polar compounds that were used as test solutes included ketones, aldehydes, esters, nitro-containing compounds, alcohols, phenols, fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Slater and co-workers tried to use a silicone composite membrane to separate methyl ethyl ketone from ethanol, but with little success. In addition, many nonmembrane methods, such as solution-phase complexation, chromatography, and supercritical fluid gas chromatography, have been used to separate ketones, alcohols, and hydrocarbons on a laboratory scale.…”
Section: Resultsmentioning
confidence: 99%
“…Slater and co-workers tried to use a silicone composite membrane to separate methyl ethyl ketone from ethanol, but with little success. In addition, many nonmembrane methods, such as solution-phase complexation, chromatography, and supercritical fluid gas chromatography, have been used to separate ketones, alcohols, and hydrocarbons on a laboratory scale.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with "brush" structure bonded phases, hydrosiloxane polymer-encapsulated particles provide a more inert surface which is suitable for the separation of polar compounds, even when using weakly polar CO 2 as the mobile phase [7,9]. In this study, the separation capabilities of these particles were examined using normal hydrocarbons as test solutes, and the results are illustrated in Figure 3.…”
Section: Particle Surface Chemical Modification and Peak Capacity In mentioning
confidence: 98%
“…In SGC, the mobile phase can change from a supercritical fluid to a gas [4] or from a superheated liquid to a gas [5], or remain as a solvating gas [6] throughout the column length. Both adsorbents [6] and bonded phases [7] have been used in SGC to perform solvating gas-solid chromatography (SGSC) and solvating gasliquid chromatography (SGLC). An analysis of the peak capacities indicated that packed column SGC provided similar separation capability to open tubular column gas chromatography [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that solvating gas chromatography (SGC) provides high-speed 1 and high-efficiency separations 2 and is even suitable for the separation of polar compounds such as free acids and amines 3 when using microparticle packed capillary columns and CO 2 as mobile phase. When CO 2 is used as the mobile phase, the column inlet and outlet behave as supercritical fluid chromatography (SFC) and gas chromatography (GC), respectively.…”
mentioning
confidence: 99%